Variable involvements of mantle plumes in the genesis of mid-Neoproterozoic basaltic rocks in South China: A review - Wang, Xuan-ce; Li, X.; Li, W.; Li, Zheng-Xiang (Elsevier Science BV, 2009)
Ca. 825-720 Ma global continental intraplate magmatism is generally linked to mantle plumes or a mantle superplume that caused rifting and fragmentation of the supercontinent Rodinia. Widespread Neoproterozoic igneous rocks in South China are dated at ca. 825-760 Ma. There is a hot debate on their petrogenesis and tectonic affiliations, i.e., mantle plume/rift settings or collision/arc settings. Such competing interpretations have contrasting implications to the position of South China in the supercontinent Rodinia and in Rodinia reconstruction models. Variations in the bulk-rock compositions of primary basaltic melts can provide first order constraints on the mantle thermal-chemical structure, and thus distinguish between the plume/rift and arc/collision models. Whole-rock geochemical data of 14 mid-Neoproterozoic (825-760 Ma) basaltic successions are reviewed here in order to (1) estimate the primary melts compositions; (2) calculate the melting conditions and mantle potential temperature; and (3) identify the contributions of subcontinental lithosphere mantle (SCLM) and asenthospheric mantles to the generation of these basaltic rocks. In order to quantify the mantle potential temperatures and percentages of decompression melting, the primary MgO, FeO, and SiO2 contents of basalts are calculated through carefully selecting less-evolved samples using a melting model based on the partitioning of FeO and MgO in olivine. The mid-Neoproterozoic (825-760 Ma) potential temperatures predicted from the primary melts range from 1390 C to 1630 C (mostly N1480 C), suggesting that most 825-760 Ma basaltic rocks in South China were generated by melting of anomalously hot mantle sources with potential temperatures 80-200 C higher than the ambient Middle Ocean Ridge Basalt (MORB)-source mantle.The mantle source regions of these Neoproterozoic basaltic rocks have complex histories and heterogeneous compositions. Enriched mantle sources (e.g., pyroxenite and eclogite) are recognized as an important source for the Bikou and Suxiong basalts, suggesting that their generations may have involved recycled components. Trace elements variations show that interactions between asthenospheric mantle (OIB-type mantle) and SCLM played a very important role in generation of the 825-760 Ma basalts. Our results indicate that the SCLM metasomatized by subduction-induced melts/fluids during the 1.0-0.9 Ga orogenesis as a distinct geochemical reservoir that contributed significantly to the trace-elements and isotope inventory of these basalts.The continental intraplate geochemical signatures (e.g., OIB-type), high mantle potential temperatures and recycled components suggest the presence of a mantle plume beneath the Neoproterozoic South China block. We use the available data to develop an integrated plume-lithosphere interaction model for the ca. 825-760Ma basalts. The early phases of basaltic rocks (825-810 Ma) were most likely formed by melting within the metasomatized SCLM heated by the rising mantle plume. The subsequent continental rift allowed adiabatic decompression partial melting of an upwelling mantle plumes at relatively shallow depth to form the widespread syn-rifting basaltic rocks at ca. 810-800 Ma and 790-760 Ma.